Eficácia clínica da raspagem de boca toda associada com dispersão de partículas S-PRG para o tratamento não cirúrgico de periodontite estágios III e IV: estudo de série de casos - acompanhamento de 6 meses - Melo, Antonio Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Objective: This study aims to evaluate the efficacy of S-PRG (Shofu®) dispersion as an adjunct in non-surgical periodontal treatment in patients with stage III/IV periodontitis. Material and Methods: Patients with stage III and IV periodontitis presenting radiographic bone loss and a minimum of 18 teeth were included. Smokers, systemically compromised individuals, and patients who had received periodontal treatment within the previous 6 months were excluded. Treatment groups were as follows: (FMS) full-mouth scaling with distilled water, and (FMS+S-PRG) full-mouth scaling associated with the S-PRG adjunct. All procedures were performed using standardized ultrasonic instrumentation. The clinical parameters evaluated were: plaque index (PI), bleeding on probing (BOP), probing depth (PD), and clinical attachment level (CAL), at baseline and after 6 months. Results: Both groups, FMS and FMS+S-PRG, showed a significant reduction in bleeding on probing, plaque index, and probing depth between baseline and 6 months. A decrease in the number of shallow, moderate, and deep pockets was observed in both groups. In the FMS+S PRG group, there was a significant reduction in deep pockets (≥7 mm) and an increase in sites up to 4 mm after 6 months, as well as improvement in psychosocial parameters in both groups. Conclusion: This study demonstrates promising results regarding the use of S-PRG dispersion as an adjunct in the treatment of periodontitis, particularly for deep pockets (≥7 mm). This adjunct contributed to an increased proportion of healthy sites after 6 months, as well as improvements in the psychosocial health of the individuals

Objetivo: Este estudo tem como objetivo avaliar a eficácia da dispersão de S-PRG (Shofu®) como adjuvante no tratamento periodontal não cirúrgico em pacientes com periodontite estágio III/IV. Materiais e Métodos: Foram incluídos pacientes com periodontite estágios III e IV, apresentando perda óssea radiográfica e no mínimo 18 dentes. Fumantes, indivíduos com comprometimento sistêmico e pacientes que haviam recebido tratamento periodontal nos últimos 6 meses foram excluídos. Os grupos de tratamento foram: (FMS) raspagem em boca toda com água destilada e (FMS+S-PRG) raspagem em boca toda associada ao adjuvante S-PRG. Todos os procedimentos foram realizados com instrumentação ultrassônica padronizada. Os parâmetros clínicos avaliados foram: índice de placa (PI), sangramento à sondagem (BOP), profundidade de sondagem (PD) e nível clínico de inserção (CAL), no início e após 6 meses. Resultados: Ambos os grupos, FMS e FMS+S-PRG, apresentaram redução significativa no sangramento à sondagem, no índice de placa e na profundidade de sondagem entre o início e 6 meses. Observou-se uma diminuição no número de bolsas rasas, moderadas e profundas em ambos os grupos. No grupo FMS+S-PRG, houve uma redução significativa nas bolsas profundas (≥7 mm) e um aumento no número de sítios com até 4 mm após 6 meses, além de melhora nos parâmetros psicossociais em ambos os grupos. Conclusão: Este estudo demonstra resultados promissores quanto ao uso da dispersão de S-PRG como adjuvante no tratamento da periodontite, especialmente para bolsas profundas (≥7 mm). Esse adjuvante contribuiu para um aumento na proporção de sítios saudáveis após 6 meses, bem como para melhorias na saúde psicossocial dos indivíduos.
Clinical efficacy of full-mouth scaling associated with S-PRG particle dispersion for the non-surgical treatment of stage III and IV periodontitis: a case series study – 6-month follow-up
Keywords: Periodontite; Bolsa periodontal; Raspagem Dentária; Periodontal pocket; Dental scaling; Periodontitis